Engaging Students in Reading Tasks Through the Shared Reading Strategy (2023)
ABSTRACT: This study is an action research project carried out with seventh graders at Institucion Educativa Javiera Londoño Sevilla; a public institution located in Medellín. The aim of this project was to enhance student engagement through the implementation of the Shared Reading strategy in reading tasks in the English class. The data collection methods included two student surveys, observations registered in the student-teacher’s journal, two students' self-assessment tasks and a Cooperating Teacher interview. Data were analyzed using the triangulation method with all the tools. The results showed that promoting reading as a collaborative experience through the Shared Reading strategy, allows students to increase their confidence to participate, interact and commit to reading tasks in the English class. It also can help create an enjoyable environment where students feel comfortable and where their interest in learning is enhanced